Liver Transplantation for Autoimmune Hepatitis: 20 Years of Tertiary Centre Experience - Sağlam, Osman; Harputluoğlu, Muhsin Murat Muhip; Bilgiç, Yılmaz; Yılmaz, Sezai; Yağın, Fatma Hilal; Efe, Cumali (Turkish Journal of Gastroenterology, 2024)
Background/Aims: We analyzed the frequency of complications and survival rates in patients with autoimmune hepatitis (AIH) who underwent liver transplantation at a high-volume transplant center. Materials and Methods: Patients who underwent transplantation for AIH at the İnönü University Liver Transplantation Institute between January 2002 and December 2021 were included. Patients with a confirmed diagnosis of AIH, without concomitant chronic liver disease, were included in the study. Results: We included 51 patients (31 female) with a median age of 38.5 years (18-65 years). The 12-month and 60-month survival rates were 86.3% and 80.9%, respectively. During a median 2.22 years follow-up, 9 patients died. Six patients died due to systemic infection, 1 due to biliary complications, and 2 patients due to graft rejection. Autoimmune hepatitis recurrence developed in 6 (11%) patients. Overall, biliary complications developed in 56% (28/51) of patients following liver transplantation, and graft rejection occurred in 22% (11/51) of patients. Conclusion: Our results suggest that the outcome of AIH following liver transplantation is good, with a survival rate of up to 80%. Post transplant biliary complications are common; therefore, close follow-up is necessary. Cite this article as: Sağlam O, Harputluoğlu MMM, Bilgiç Y, Yılmaz S, Yağın FH, Efe C. Liver transplantation for autoimmune hepatitis: 20 years of tertiary centre experience. Turk J Gastroenterol. 2025;36(3):145-151.